Religiosity and sexual risks among Croatian college students, 1998-2008 - Štulhofer, Aleksandar (Array, 2011)
Substantial increase in religious identification was observed in most European post-communist countries. As religiosity has been associated with STI/HIV vulnerability among young people, this paper examined the impact of religious upbringing and personal religiosity (religiousness) on sexual risks among the University of Zagreb first-year undergraduate students using data collected in 1998, 2003, and 2008. Female participants who reported strict religious upbringing were less knowledgeable about human sexuality than other women. Religiousness was negatively correlated with basic knowledge of human sexuality, but again only among women. Contrary to expectations, no significant associations were found between religious upbringing or religiousness and condom use. Both measures of religiosity, however, were related to the decreased odds of sexual debut among young women. In the case of male participants, the impact of religiosity was marginal. Religious upbringing was associated (negatively) with sexual literacy and sexual debut – but only at the beginning of the observed period. Overall, religiosity does not seem to substantially reduce STI/HIV-related risk taking, particularly among men. Since the observed increase in the proportion of sexually active students during the 1998-2008 period was not matched by an increase in condom use, reducing STI/HIV vulnerability among Croatian youth remains an essential task.